The role of intellectual capital in crisis management: An exploratory study of the opinions of a sample of employees at the General Company for Southern Fertilizers Manufacturing (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to identify the role of intellectual capital through its dimensions (human capital, structural capital, relational capital) in crisis management in the Iraqi economy. The research was conducted in the General Company for the Southern Fertilizer Industry in Basra Governorate. By adopting the descriptive analytical approach with a simple random sample consisting of 346 workers from various job centers and scientific specializations. Relying on the statistical analysis program (SPSS 25), the results showed the presence of a positive, moderately significant effect between intellectual capital and crisis management, the dimensions of which were adopted related to the pre-crisis stage, during the crisis, and after overcoming the crisis. It is possible to benefit from the research results in that The company is keen to increase its interest in increasing the skills and competencies of its workers by realizing the role of these competencies in the continuation and survival of the company and its overcoming various crises.